Characterising infant and young child feeding practices and the consumption of poultry products in rural Tanzania: A mixed methods approach. Issue 2 (2nd November 2017) - de Bruyn, Julia; Bagnol, Brigitte; Darnton‐Hill, Ian; Maulaga, Wende; Thomson, Peter C.; Alders, Robyn
Abstract: Suboptimal breastfeeding practices, early initiation of complementary feeding, and monotonous cereal‐based diets have been implicated as contributors to continuing high rates of child undernutrition in sub‐Saharan Africa. Nutrition‐sensitive interventions, including agricultural programs that increase access to nutrient‐rich vegetables, legumes, and animal‐source foods, have the potential to achieve sustainable improvements in children's diets. In the quest to evaluate the efficacy of such programs in improving growth and development in the first 2 years of life, there is a role for mixed methods research to better understand existing infant and young child feeding practices. This analysis forms part of a longitudinal study assessing the impact of improvements to poultry health and crop production on diets and growth of 503 randomly selected children from eight rural communities in Manyoni District in central Tanzania. Using an explanatory sequential design, the quantitative phase of data collection was conducted between May 2014 and May 2016, comprising six monthly structured questionnaires, four monthly household‐level documentation of chicken and egg consumption, and fortnightly records of children's breastfeeding status. The subsequent qualitative phase involved in‐depth interviews with a subset of 39 mothers in October 2016. Breastfeeding was almost universal (96.8%) and of long duration (mean = 21.7 months, SD  = 3.6), but early initiation of complementary feeding was also common (74.4%; mean = 4.0 months, SD  = 1.8), overwhelmingly driven by maternal perceptions of insufficient milk supply (95.0%). Chicken and eggs were infrequently eaten, but close associations between maternal and child consumption patterns ( p  < .001) suggest the potential for strategies that increase household‐level consumption to bring nutritional benefits to young children.